Internal audit functions: an empirical study of public and private sectors in Nigeria - Madawaki, Abdulkadir; Ahmi, Aidi; Ahmad, Halimah @ Nasibah (OMJP Alpha Publishing, 2018)
The study examines the similarities and differences between the private and public sectors internal audit functions in Nigeria. The features examined include the hierarchical position of the internal audit functions, outsourcing of internal audit activities, reporting relationship of the internal auditor, and the coordination between internal and external auditors. A survey of internal audit managers of both sectors was undertaken to establish their current practices. The results revealed that there are no much differences in the hierarchical positioning of the internal audit function in both sectors. A substantial difference was found in the reporting lines of internal auditors in both sectors. The results further showed that private sector outsources internal audit activities more than the public sector and a slight difference exists between the two sectors about the level of coordination between internal and external auditors. Finally, the result indicated that private sector experiences a reduction in external audit fees compares to its counterpart in the public sector.